Observation of Frog Species in State University of Malang as a Preliminary Effort on Frog Conservation - Wulandari, Dian Ratri; Habibi, Muhammad; Listyorini, Dwi (Journal of Tropical Life Science, 2013)
Frog is an amphibian which widely distributed around the world. Indonesia houses 450 species which represent 11% of frog species in the world. In Java Island living 42 species of frogs and toads. Frogs can be used as an environment indicator due to the presence of frog in a particular place indicates that the place is stay natural and unpolluted. State University of Malang Campus #1 which is located in the heart of Malang District has been developing rapidly, currently. Thus, it requires for the construction of new various facilities to support it widen activities. Extensive construction can be destructive even damaging to the habitat of frog, which potentially threat the frog life, if it does not take a consideration on the environmental impact, carefully. This study aimed to identify the species of frog which is survives in State University of Malang with consideration of the frog species found in 1995. Species identification conducted by observing the morphologicalcharacter. This study found four species with three species which are survive and as found in 1995; those are Duttaphrynus melanostictus, Polypedates leucomystax, and Kaloula baleta; and one new species that is Rana chalconota. This study also reveals there are four species which are extinct; those are Fejervarya cancrivora, Fejervarya limnocharis, Ingerophrynus biporcatus, and Occidoziga lima. This situation shows the decreasing amount of species from 7 to 4 within 17 years. This result indicates that there is a serious environmental degradation which caused the losing of frog habitats. Further research is needed to study the ecological condition changing in order to save the frog species.